2009
DOI: 10.1111/j.1476-5381.2008.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐converting enzyme 1 promotes re‐sensitization of neurokinin 1 receptor‐dependent neurogenic inflammation

Abstract: Background and purpose:The metalloendopeptidase endothelin-converting enzyme 1 (ECE-1) is prominently expressed in the endothelium where it converts big endothelin to endothelin-1, a vasoconstrictor peptide. Although ECE-1 is found in endosomes in endothelial cells, the role of endosomal ECE-1 is unclear. ECE-1 degrades the pro-inflammatory neuropeptide substance P (SP) in endosomes to promote recycling and re-sensitization of its neurokinin 1 (NK1) receptor. We investigated whether ECE-1 regulates NK1 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…In addition to its strong expression in endothelial cells, ECE-1 is expressed in neurons in different areas of the CNS, including areas relevant to AD, and contributes to the metabolism of different neuropeptides as well as receptor resensitization within the endosomal system (45,46). The intracellular ECE-1d and ECE-1b isoforms are localized in recycling endosomes with ECE-1b present also in late endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its strong expression in endothelial cells, ECE-1 is expressed in neurons in different areas of the CNS, including areas relevant to AD, and contributes to the metabolism of different neuropeptides as well as receptor resensitization within the endosomal system (45,46). The intracellular ECE-1d and ECE-1b isoforms are localized in recycling endosomes with ECE-1b present also in late endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, like SP, CGRP, or somatostatin, ECE-1 internalized with the ET-1/ETAR complex into early endosomes, cleaved ET-1, and may thereby regulate the function of ET-1 in murine DRG neurons during an itch response (27,33). Recently, it has been shown that ECE-1 participates in the modulation of neurogenic inflammation in mice in vivo (66). However, we believe that the results of the current study demonstrate for the first time that ECE-1 is also directly involved in ET-1-mediated pruritus and neuronal cell signaling in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…By degrading SP and CGRP in acidified endosomes, ECE-1 promotes recycling and resensitization of receptors that mediate neurogenic inflammation and pain (52,53). An ECE-1 inhibitor prevents resensitization of SP-induced plasma extravasation, providing evidence for an antiinflammatory effect of ECE-1 inhibitors (53,97). Thus, in the case of ␤arrs and ECE-1, therapies that specifically target GPCR signaling in endosomes without affecting signaling at the plasma membrane are a viable and novel pharmacological strategy.…”
Section: Physiological Outcomes Of Endosomal Sig-mentioning
confidence: 99%
“…This strategy may offer improved selectivity with fewer side effects than targeting more proximal steps of receptor signaling. Indeed, drugs that either target endosomal signaling events (53,(95)(96)(97) or that are specifically delivered to endosomes (98) have powerful effects. The challenge will be to design drugs that target endosomal signaling relevant to disease.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%